МЕТОДОЛОГІЧНІ ОСНОВИ ПРОВЕДЕННЯ ЕКСПЕРИМЕНТАЛЬНО-ФОНЕТИЧНОГО ДОСЛІДЖЕННЯ ФОНОСЕМАНТИЧНИХ КОМПЛЕКСІВ В СУЧАСНОМУ АНГЛОМОВНОМУ ХУДОЖНЬОМУ КІНОДИСКУРСІ - Насікан З. С. (International Journal of Innovative Technologies in Social Science, 2019)
This paper deals with the methodology of experimental research of phonosemantics complexes that are able to actualize the emotional function in modern English film discourse. It is claimed that such type of investigation must be held by means of perceptual and acoustic analyses. The article contains the program of investigation, its main stages including corpus, participants (auditors- informants and auditors-phoneticians), and their tasks. Acoustic analysis was directed on proving the results of perceptive analyses by counting and evaluation of tonal, dynamic and temporal characteristics. The given methodological grounds create a fundamental basis for investigation of phonosemantic means and complexes of modern English motion pictures.